Transitional Pain Care in Quebec: Did We Forget Our Youths? A Brief Research Report - Kudrina, Irina; Bartlett, Gillian; Pagé, M. Gabrielle; Shir, Yoram; Tourian, Leon; Choinière, Manon; Vedel, Isabelle (Frontiers in Pain Research, 2022)
Adolescents and young adults (AYAs) represent a unique population with distinct psycho-social risks and care needs. About 10% of AYAs live with chronic pain (CP) and transition to adult pain care between 16 and 25 years of age. These transitions in care happen simultaneously with other bio-psycho-social changes and require flexible multi-disciplinary support models. As it stands, transitional pain care appears suboptimal, fragmented, and opportunistic in Quebec (Canada). The objective of this Brief Report is, therefore, to present our study findings and propose a multi-disciplinary transitional framework vision applicable to AYAs living with CP. Data were collected using a sequential-consensual qualitative design with a longitudinal participatory component. The consecutive stages of this work included an exploratory stage, semi-structured interviews with primary care providers, and inter-disciplinary deliberative stakeholder consultation groups. The deductive inductive thematic approach and the three-level Health Care Transition Research Consortium's theoretical framework were used to analyze the data. A representative group of stakeholders discussed findings from the first two steps, made fifteen actionable recommendations and formulated their vision of a transitional pain care model that can be further adapted in other settings. The study results present important insights into various psycho-social factors associated with transitional pain care for AYAs.